Nature's Tapestry: Ecocritical Exploration of Identity in Jeanette Armstrong's 'Whispering in the Shadows (International Journal of Food and Nutritional Sciences, 2022)
In aboriginal cultures around the world, where the idea of land ownership is absent and animistic beliefs entwine Nature with one's basic sense of self, the role of Nature is of utmost importance. Contrastingly, modern capitalism thrives on exploitingNature, leading to unchecked misuse and an escalating climatic problem. Writing about environmental degradation has seen a recent uptick in engagement from contemporary authors in response to this worldwide concern. Whispering in the Shadows, a book by Jeanette Armstrong, is examined ecocritically in this study. Armstrong is well-known for being a Native Canadian novelist and environmental activist, and his Okanagan heritage greatly influenced this literary investigation. The study explores how the natural world is a foundation for creating a Native Canadian identity in the story.